2013
DOI: 10.1007/s12272-013-0079-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freeze dried bovine amniotic membrane extract on full thickness wound healing

Abstract: This study explored the feasibility of development of solubilized amniotic membrane extract (AME) as a potential wound healing substrate with improved efficacy. Bovine amniotic membrane was extracted using a mixture of acetic acid and 2-mercaptopropionic acid under sonication, which was followed by the frozen, and then lyophilized processes. The effects of AME on cell migration and growth properties were evaluated from 0 to 24 h of post injury using primary human foreskin fibroblast monolayer culture with one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…The porcine small intestine submucosa that has been lyophilized and sterilized has been recently shown to provide similar benefits to those provided by fish skin-based products for enhancing healing dermal wounds (Mostow et al, 2005). Similarly, lyophilized bovine amniotic membrane has been effective in wound healing applications (Kang et al, 2013). The silk protein, fibroin, is an effective scaffolding material providing a fine mesh for the cells to grow and enhance wound healing (Hasatsri et al, 2015).…”
Section: Biomaterial-based Wound Therapiesmentioning
confidence: 99%
“…The porcine small intestine submucosa that has been lyophilized and sterilized has been recently shown to provide similar benefits to those provided by fish skin-based products for enhancing healing dermal wounds (Mostow et al, 2005). Similarly, lyophilized bovine amniotic membrane has been effective in wound healing applications (Kang et al, 2013). The silk protein, fibroin, is an effective scaffolding material providing a fine mesh for the cells to grow and enhance wound healing (Hasatsri et al, 2015).…”
Section: Biomaterial-based Wound Therapiesmentioning
confidence: 99%
“…Studies using lyophilized biological medications like amnion and porcine skin demonstrated that one of their important advantages was obviating the need for frequent painful dressings associated with bleeding and which sometimes requires general anesthesia, and also, these lyophilized biological dressings are more economical, easy to handle and apply (Gajiwala & Gajiwala, 2004;Hosseini et al, 2009). Moreover, Kang et al showed that the lyophilization method can keep the advantages of fresh bovine amniotic membrane in the wound healing process (Kang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Their effectiveness was confirmed both in experimental studies and clinical trials. Finally, some commercial amnion‐derived products have been developed for ophthalmic use, for example, Amniotic Cytokine Extract (ACE), Regener‐Eyes, Optiserum and PDA‐AF …”
Section: Placental Tissues As Materials For Use In Medicinementioning
confidence: 99%
“…Finally, some commercial amnion-derived products have been developed for ophthalmic use, for example, Amniotic Cytokine Extract (ACE), Regener-Eyes, Optiserum and PDA-AF. 58,[68][69][70][71][72][73] Amnion transplants are also administrated (among others) on cut skin wounds, post-excision wounds, bullous skin diseases, pressure ulcers, wounds arising near or around the nervous tissue, on damages to the mouth and eye surface.…”
Section: Classical Applications Of Placental Tissues In Wound Healingmentioning
confidence: 99%